TUHAN DALAM KEPERCAYAAN MANUSIA MODERN (Mengungkap Relasi Primordial Antara Tuhan dan Manusia) - Mahfud (CENDEKIA: Jurnal Studi Keislaman, 2015)
God, is one of the most important parts of a person's religious life. Godless means human nature as human beings have been violated. For every mankind that God is transcendent unity so belief in God itself occupies a primordial position in the level of one's faith. However, the current conception of the existence of the primordial relationship between humans and God that has been replaced by the new idols that materialism, capitalism, and other isms. Which is then set aside God in concrete reality, this is in line with what is perceived by Karl Marx about God itself. And how he position God in someone's life and someone’s religious life about importance of God in life. So, in the belief of modern humans, religion is only seen as something that only has a purpose for life in the hereafter, but not in this world.